Motor-nerve excitability changes in critically ill patients. Issue 3 (March 2016) - Koch, S.; Bierbrauer, J.; Haas, K.; Wolter, S.; Spies, C.; Weber-Carstens, S.
Abstract : Objective: Abnormal membrane depolarization in different tissues occurs in critically ill patients as well as in patients suffering critical illness polyneuropathy (CIP) after ICU treatment. The aim of this study was to investigate the pathophysiological differences in motor nerve membrane polarization and excitability in CIP patients suffering weakness versus critically ill patients without CIP (ICU-controls) during their ICU stay. Methods: ICU patients underwent electrophysiological nerve-conduction studies and were categorized as either ICU-control or CIP patients. Subsequently, excitability parameters were recorded as current-threshold-relationship, stimulus-response-behavior, threshold-electrotonus, and recovery-of-excitability from the abductor pollicis brevis following median-nerve stimulation. Results: 26 ICU patients were enrolled and categorized as 12 ICU-controls or 14 CIP patients. Compared to 31 healthy subjects, ICU-controls exhibited signs of membrane depolarization [reduced superexcitability, p = 0.003]. CIP patients displayed a more pronounced membrane depolarization [reduced superexcitability, p < 0.0001] accompanied by reduced membrane excitability [reduced strength-duration time constant, p < 0.0001], and a reduced "paradoxical K+ conductance" over the membrane in the presence of membrane depolarization. Conclusions: Abnormal motor-nerve membrane depolarization is a general finding in ICU patients. Accordingly, reduced membrane excitability and "paradoxical reduced K+ conductance" over the membrane could be responsible for weakness in CIP patients.